Humaria setimarginata (Pyronemataceae, Ascomycota), a new species from Mexico - Sánchez-Flores, Marcos; Raymundo, Tania; Van Vooren, Nicolas; Martínez González, César Ramiro; García-Jiménez, Jesús (Instituto de Ecología, A.C., 2023)
Background and Aims: Humaria (Pyronemataceae, Ascomycota) is an ectomycorrhizal genus of fungi, mainly distributed in temperate forest. It is characterized by cupuliform to discoid apothecia that are covered with abundant hairs throughout the exterior of the brown ascomata, and by ellipsoid, hyaline, warty ascospores. There are 66 accepted species of which only one has been recorded in Mexico. The present study aims to describe a new species of Humaria with morphological, ecological and molecular data, found in Quercus forests from Tamaulipas, Mexico. Methods: The specimens were collected in 2019 in the Victoria municipality, Tamaulipas, Mexico. Description and morphological studies were performed according to traditional mycological techniques. Studied material was deposited in the José Castillo Tovar Mycological Herbarium of the Instituto Tecnológico de Ciudad Victoria (ITCV) and the Escuela Nacional de Ciencias Biológicas Herbarium (ENCB) of the Instituto Politécnico Nacional. Phylogenetic analyses were performed using ITS and LSU sequences of the nuclear rDNA. Key results: Humaria setimarginata sp. nov. is described and illustrated. This species is well differentiated by its morphological, molecular and ecological characteristics. It forms typically cupuliform apothecia with straight margin, abundant dark brown colored short hairs at the margin, and a greyish-white hymenium. It presents a dextrinoid reaction in the ectal excipulum in contact with Melzer´s reagent. It grows around Quercus rysophylla and Q. polymorpha in oak forests. Conclusions: Humaria setimarginata is the second species of this genus reported in Mexico, after Humaria hemisphaerica. There are several collections under the name Humaria sp. that need a revision, to expand the diversity knowledge of this genus in this country. It is possible that several species exist, considering that this genus is ectomycorrhizal and the diversity of its potential hosts is high.